Jawabanmu

2014-09-08T18:59:19+07:00
Karena perpangkat 3 dibagi oleh berpangkat 2 maka hasil berpangkat 1 atau ax+b

fx= (ax+b)(x^2-x-6)+(5x-2)  = ax³   +(b-a)x²  -(6a -  b+5)x     -6b-2
   = (ax+b)(x-3)(x+2)+5x-2 akar x3=-2 ..... (1)

fx =(ax+b)(x^2-2x-3) +(3x+4)=ax³  -(2a-b)x²  -(3a+2b+3)x    -3b+4
   = (ax+b)(x-3)(x+1)+3x+4...  nilai x1=3 dan x2=1  .... (2)

(2) ... x= - 2
         (-2a+b)(-5)(-1)-6+4=0
         -10 a + 5b -2=0  ............(3)
(1) .... x= 1
           (a+b)(-2)(2)+6+4
           -4a -4b +10=0 ............(4)

dari (3) dan (4) diperoleh a    dan b ..... ax+b=